Effect of remdesivir on viral dynamics in COVID-19 hospitalized patients: a modelling analysis of the randomized, controlled, open-label DisCoVeRy trial. (2nd March 2022) - Lingas, Guillaume; Néant, Nadège; Gaymard, Alexandre; Belhadi, Drifa; Peytavin, Gilles; Hites, Maya; Staub, Thérèse; Greil, Richard; Paiva, Jose-Artur; Poissy, Julien; Peiffer-Smadja, Nathan; Costagliola, Dominique; et al.
Abstract: Background: The antiviral efficacy of remdesivir in COVID-19 hospitalized patients remains controversial. Objectives: To estimate the effect of remdesivir in blocking viral replication. Methods: We analysed nasopharyngeal normalized viral loads from 665 hospitalized patients included in the DisCoVeRy trial (NCT 04315948; EudraCT 2020-000936-23), randomized to either standard of care (SoC) or SoC + remdesivir. We used a mathematical model to reconstruct viral kinetic profiles and estimate the antiviral efficacy of remdesivir in blocking viral replication. Additional analyses were conducted stratified on time of treatment initiation (≤7 or >7 days since symptom onset) or viral load at randomization (< or ≥3.5 log10 copies/10 4 cells). Results: In our model, remdesivir reduced viral production by infected cells by 2-fold on average (95% CI: 1.5–3.2-fold). Model-based simulations predict that remdesivir reduced time to viral clearance by 0.7 days compared with SoC, with large inter-individual variabilities (IQR: 0.0–1.3 days). Remdesivir had a larger impact in patients with high viral load at randomization, reducing viral production by 5-fold on average (95% CI: 2.8–25-fold) and the median time to viral clearance by 2.4 days (IQR: 0.9–4.5 days). Conclusions: Remdesivir halved viral production, leading to a median reduction of 0.7 days in the time to viral clearance compared with SoC. The efficacy was larger in patients with high viral load at randomization.